2002
DOI: 10.1177/0734242x0202000108
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of waste incinerator air-pollution-control residues with FeSO4: Concept and product characterisation

Abstract: This paper describes a new concept for treatment of air pollution-control (APC) residues from waste incineration and characterises the wastewater and stabilised residues generated by the process. The process involves mixing of APC-residues with a ferrous sulphate solution and subsequent oxidation of the suspension (Ferrox-process 1996). The process results in a significant reduction in the leaching of salts and heavy metals from the residue, by washing out most of the salts and by binding the heavy metals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 6 publications
1
53
1
1
Order By: Relevance
“…The results for S were expected, because S was added as FeSO 4 as a part of the treatment and in highest quantities in the case of SD (see Table 1). A comparison of the achieved results with the laboratory studies reported in Jensen et al 8 and Lundtorp et al 9,10 shows that the leaching properties are the same even though the process has been developed with changes in both the process and the scale. This indicates that the leaching properties of treated residues are very robust and only slightly affected by variations in the process.…”
Section: Leaching From Solidsmentioning
confidence: 57%
See 2 more Smart Citations
“…The results for S were expected, because S was added as FeSO 4 as a part of the treatment and in highest quantities in the case of SD (see Table 1). A comparison of the achieved results with the laboratory studies reported in Jensen et al 8 and Lundtorp et al 9,10 shows that the leaching properties are the same even though the process has been developed with changes in both the process and the scale. This indicates that the leaching properties of treated residues are very robust and only slightly affected by variations in the process.…”
Section: Leaching From Solidsmentioning
confidence: 57%
“…[8][9][10] The process is based on the established facts that many trace metals in natural environments, such as those in soils and sediments, are bound to iron oxides 11 and that engineered iron oxides are able to bind substantial amounts of trace metals. 12 In the Ferrox process, the alkaline APC residue is mixed with an FeSO 4 solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aeration oxidised the precipitated ferrohydroxide to ferrihydrite and the suspension was then separated into treated residue and wastewater. This process was reported to leach out large amounts of salts (Cl, Na, K and Ca) but low concentrations of trace metals (Pb and Cd) from FA residues (Lundtorp et al 2002). Hu (2005) studied the effectiveness of mixing FeSO 4 and Fe 2 (SO 4 ) 3 solutions with FA residues in order to stabilize heavy metals and they concluded that the solution reacted with the FA to form Ca 4 Fe 9 O 17 , which coated the surface of ash particles, and for that reason the heavy metal releasing was decreased.…”
Section: The Ferrox ® Processmentioning
confidence: 98%
“…The Ferrox ® -process was developed in Denmark as an on-site treatment for FA residues prior to landfill disposal (Lundtorp et al 2002;Jensen et al 2002). The process consisted in mixing of three mayor units that were ferrous sulphate solution, recycled water and FA residues; suddenly the oxidation of ferrous iron took place followed by pH adjustment with either additional FeSO 4 or H 2 SO 4 and finally, in a plate-and-frame filter press, the treated residue was dewatered.…”
Section: The Ferrox ® Processmentioning
confidence: 99%